Pengaruh Dukungan Organisasi dan Work Value Terhadap Komitmen Organisasi Karyawan Generasi Y - Fahri, Syahrul; Mariatin, Emmy; Zahreni, Siti (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
The aim of this research is to know the influence of Organizational Support Influence and Work Value towards Organizational commitment of the Y Generation Workers. The measurent used in this researce is the organization commitment scale and the work value scale. This research involves 211 workers in the Y generation in the Sakit Sari Mutiara Hospital Medan. The implication of this research hopes that organization should offer honors and or positive attitudes towards the Y generation, so that the workers’ organization support perception of the generation Y will show increase and improvement, with this increase perception given towards of the organization support the Y generation will enhance their affective commitment, continuance commitment and normative commitment.